Įrodymų leistinumo reikšmė Lietuvos civiliniame procese - Bartkus, Jurgis (Teisė, 2021)
The article analyses the importance of the admissibility of evidence in Lithuanian civil proceedings. The analysis of various sources of law allows to link the admissibility of evidence in civil proceedings not only with one of the features of evidence, but also with the objectives of this institute in civil proceedings: ensuring the quality of proof, the cost-efficient process, a fair and just trial, and other values.The reduction of the importance of the admissibility of evidence is essentially influenced by aspects related to the whole evidentiary process – the principle of free evaluation of evidence, the purpose of determination of material truth, and procedural norms establishing the judge as the final assessor of admissibility of evidence and facts. The objectives of the admissibility of evidence in civil proceedings make it necessary to find possible solutions that ensure a more appropriate relationship between the admissibility of evidence and the reasons of its importance.Straipsnyje analizuojama įrodymų leistinumo reikšmė Lietuvos civiliniame procese. Atlikta įvairių teisės šaltinių analizė leidžia įrodymų leistinumą civiliniame procese sieti ne tik su vienu iš įrodymų požymių, bet ir su šio instituto civiliniame procese įgyvendinamais tikslais, t. y. įrodinėjimo kokybės, ekonomiško proceso, sąžiningo ir teisingo proceso ir kitų vertybių užtikrinimu.Įrodymų leistinumo reikšmei sumažinti esminę įtaką daro su visu įrodinėjimo procesu susiję aspektai – laisvo įrodymų vertinimo principas, materialiosios tiesos nustatymo tikslas ir procesinės normos, nustatančios teisėją kaip galutinį įrodymų leistinumo ir faktų nustatymo vertintoją. Dėl įrodymų leistinumo instituto tikslų civiliniame procese yra būtina rasti galimus sprendimus, kurie užtikrintų tinkamesnį šio instituto ir jo reikšmę nulemiančių priežasčių santykį